Rancang Bangun Sistem Monitoring Ketinggian Air, Suhu Dan Kekeruahan Air Pada Budidaya Ikan Lele - Giawa, Amonio; R. Tommy Gumelar; Diana Yusuf (ITB Ahmad Dahlan Jakarta, 2022)
Cultivating catfish is one of the popular fishery farming activities in Indonesia. Catfish is one of the many fish chosen for cultivation because it has a fast growth rate and can live in various air conditions. However, there are several obstacles or loss factors if not addressed quickly, such as if the air level occurs, changes in temperature conditions and also the level of air turbidity which is also not released is always reviewed regularly. This study uses a prototype method that uses system development from pre-existing systems, this writing covers the design and manufacture of hardware and software with the right detection development algorithm. Aims to produce or create a microcontroller-based system that has the ability to detect air level, temperature and air turbidity in ponds with the hope of being able to minimize the risk of losses caused by air conditions in catfish ponds. The system is equipped with an air level detector using an ultrasonic sensor, and is equipped with a DS18B20 sensor which can detect air temperature and a turbidity sensor which is used to detect the level of air turbidity and of course this system is also equipped with a microcontroller to process data from sensors used as input. The output of the air level monitoring system is an LED with red, yellow and green colors, as well as a buzzer as a marker of air level in catfish ponds. The monitoring system for temperature and also turbidity in water pools is a notification system using an I2C LCD that displays readings of sensor values. The monitoring tool has been successfully tested and is expected to be useful for increasing catfish farming results.